Timing of elective caesarean section – are we deviating from nice guideline?. (18th April 2012) - Yulia, A; Dutta, S
Abstract : Aims: To find out the numbers of elective caesarean section carried out before 39 weeks gestations and the number of infant morbidity resulting from variation from the NICE guideline. Background: Studies have shown that delivery by elective caesarean section (CS) is associated with the increase risk of transient tachypnea of the newborn (TTN) compared to vaginal delivery. Gestational age less than 39 weeks was found to be associated with increased risk of TTN in infants delivered by elective CS. NICE guideline recommend that elective CS should not routinely be carried out before 39 weeks. Methods: Retrospective study was performed during 2 months period from beginning January – February 2011. Proforma was used to collect information which was then analysed. Results: There were approximately 3184 deliveries carried out in Northumbria NHS foundation trust per year and during the 2 months study period, there were 60 elective Caesarean sections. 25% of the CS were done before 39 weeks gestations. 5 out of 15 had medical reasons, 2 out of 15 had social reasons, and the reasons for the remaining were unrecorded. No infants had TTN or admitted to SCBU in the women who had CS after 39 weeks. For those who had elective CS prior to 39 weeks gestation, 1 infant was admitted to SCBU due to TTN. Conclusions: It is important to adhere to the NICE guideline to perform elective CS after 39 weeks to reduce TTN, unless the reason to perform elective CS earlier was justified and clear documentation followed.